A201 EFFICACY OF PROTON PUMP INHIBITOR PLUS MUCOPROTECTIVE AGENT FOR ENDOSCOPIC SUBMUCOSAL DISSECTION-DERIVED ULCER; A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROL TRIAL. (1st March 2018) - Pittayanon, R; Martel, M; Barkun, A N
Abstract: Background: Currently, it is still unclear whether adding a mucoprotective agent to a Proton Pump Inhibitor (PPI) (combination treatment) results in better outcomes compared to using a PPI alone, in term of both ulcer healing and delayed bleeding in patients with post gastric-endoscopic submucosal dissection (ESD) ulcers. Aims: We conducted a meta-analysis of randomized control trials examining the efficacy of PPI alone versus combination treatment in post gastric-ESD ulcer healing as well as delayed bleeding. Methods: We performed a systematic search of MEDLINE, EMBASE, Cochrane, and ISI Web of knowledge databases, up until May 2017, for randomized trials (RCTs) comparing PPI alone versus PPI plus a mucoprotective drug in achieving ulcer healing in patients undergoing gastric ESD. Medical subject headings and keywords included PPI (omeprazole, esomeprazole, lansoprazole, dexlansoprazole, pantoprazole and rabeprazole) and mucoprotective agents (rebamipide and sucralfate). Pediatrics trials, non human subjects, not fully published articles or non-English publications were excluded. The primary outcome is scaring stage (S1 or S2) on endoscopic assessment at 4 weeks or 8 weeks after gastric ESD. Preplanned subgroup and sensitivity analyses were performed. A meta-analysis was conducted using random effect models with results reported as risk-ratios (RR) with 95% confidence intervals. Heterogeneity and publication bias were assessed and quantified. Results: From an initial 2250 citations, seven articles with 897 patients were analysed. Various PPI molecules were studied, but rebamipide was the only mucoprotective agent used in all studies. Up to 4 or 8 weeks after ESD, patients receiving combination treatment achieved a greater scaring stage significantly more often than PPIs alone (RR=1.4, 95% CI; 1.02–1.94 with heterogeneity: I 2 = 76%). There were no significant between treatment-group differences in term of delayed bleeding (RR= 0.64, 95% CI; 0.17–2.44). In sub-group analysis, no differences were noted in scaring stage between combination treatment and PPI alone at either 4 (RR=1.51, 95% CI; 1.00–2.27) or 8 weeks (RR=1.12, 95% CI; 0.78–1.62) follow-up when analyzing separately. Neither location of ulcer nor H.pylori infection were related to ulcer scaring stage whether the patients received combination treatment or PPI alone. Combination therapy was more effective than PPI alone in achieving rapid post–ESD ulcer healing amongst studies published before 2014 (RR=1.74, 95% CI; 1.39- 2.20). In contrast, no differences were noted amongst more recent studies (RR=0.92, 95% CI; 0.77–1.09). Conclusions: Combination treatment may be more effective in accelerating the process of ulcer healing in patients undergoing gastric ESD than the use of PPI alone, but does not alter delayed bleeding risk. Funding Agencies: None